The Effect of Knowledge Management and Change Management on Labor Agility in Manufactur Companies - Aisyah, Aprilia Dwi; Ananda, Febby (Growth: Journal Management and Business, 2024)
This study aims to analyze the influence of knowledge management and change management on labor agility in manufacturing companies. Knowledge management includes the acquisition, dissemination, and application of information that is essential for decision-making and employee collaboration. On the other hand, change management focuses on the company's ability to adapt to market and technological dynamics. Workforce agility is considered the ability of employees to adapt quickly and flexibly to changes that occur. The research method uses a quantitative approach with a questionnaire as the main instrument, which includes indicators of workforce agility, knowledge management, and change management. The data was analyzed using the Structural Equation Modeling (SEM) method with SmartPLS software. The results show that change management has a significant and positive effect on workforce agility, while knowledge management has no significant influence in this context. This indicates that an effective change management strategy determines workforce agility more than knowledge management. This research suggests the importance of implementing inclusive and sustainable change strategies and optimizing knowledge management through technology-based approaches and practical training. Thus, manufacturing companies can increase their competitiveness in the face of dynamic industry challenges.